2016
DOI: 10.1182/blood-2015-07-661835
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing identifies novel MPL and JAK2 mutations in triple-negative myeloproliferative neoplasms

Abstract: Key Points• Activating mutations outside exon 10 of MPL were identified in 10% (7 of 69) of triplenegative cases of ET and PMF.• JAK2-V625F and JAK2-F556V were identified in 2 triple-negative cases of ET and were shown to activate JAK-STAT5 signaling.Essential thrombocythemia (ET) and primary myelofibrosis (PMF) are chronic diseases characterized by clonal hematopoiesis and hyperproliferation of terminally differentiated myeloid cells. The disease is driven by somatic mutations in exon 9 of CALR or exon 10 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
151
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 244 publications
(160 citation statements)
references
References 34 publications
3
151
1
5
Order By: Relevance
“…Two recent studies have indeed shown that a few triplenegative patients carry activating mutations of MPL outside exon 10, and that these noncanonical mutations may be either inherited or somatically acquired. 23,24 One study has also shown that some patients carry noncanonical, activating mutations of JAK2, which appear to be germ line in most instances. 23 Finally, some patients have evidence of polyclonal hematopoiesis, and most likely do not have a true MPN.…”
Section: How We Diagnose Etmentioning
confidence: 99%
See 3 more Smart Citations
“…Two recent studies have indeed shown that a few triplenegative patients carry activating mutations of MPL outside exon 10, and that these noncanonical mutations may be either inherited or somatically acquired. 23,24 One study has also shown that some patients carry noncanonical, activating mutations of JAK2, which appear to be germ line in most instances. 23 Finally, some patients have evidence of polyclonal hematopoiesis, and most likely do not have a true MPN.…”
Section: How We Diagnose Etmentioning
confidence: 99%
“…Hereditary thrombocytosis may be associated with germ line mutations of THPO, the thrombopoietin gene, 63,64 or MPL, the thrombopoietin receptor gene. 23,24,65 Recent reports have described cases of hereditary thrombocytosis associated with noncanonical germ line mutations of JAK2. 23,[66][67][68][69] In familial ET, JAK2 (V617F) is always a somatically acquired event, as in the familial tree reported in Figure 2.…”
Section: Distinguishing Familial Et From Hereditary Thrombocytosismentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, 10-15% of patients with PMF or ET do not express any one of the three mutations and are referred to as being "triple-negative" [35]. Most recently, whole exome sequencing revealed the presence of somatic or germline MPL or JAK2 variants in 3 of 8 triple-negative patients with MPN and subsequent MPL/JAK2 entire codon sequencing among 62 ET and 49 PMF triple-negative cases revealed novel somatic or germline MPL variants in 5 of 62 cases and JAK2 variants in 5 of 57 cases [39].…”
mentioning
confidence: 99%